DOI: 10.21007/etd.cghs.2007.0073
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Brain Tumor Targeted Liposome Delivery System for Paclitaxel

Abstract: Wood, who has in every way been available as a resource be it emotionally, socially, scholarly, or administratively. I cannot overstate the importance of his involvement in my graduate career. I would like to gratefully acknowledge the enthusiastic technical support of Dr. M. Waleed Gaber for the scientific discussions on optical imaging. I would also

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 162 publications
(281 reference statements)
1
2
0
Order By: Relevance
“…The transferrin-bound design D formulation has significantly lower IC90 values over AMB-D for clinical isolates tested ( Figure 13A). This small feasibility study results (n = 1) indicated that transferrin can also potentially be used as targeting ligand, particularly for targeting CNS, where transferrin receptors are overexpressed during inflammation or tumor growth [39]. Similar results were observed with a dual drug loading formulation, with AMB and curcumin ( Figure 13B).…”
Section: In Vitro Efficacy Of Amb-ionp Fungal Clinical Isolates Of Casupporting
confidence: 71%
“…The transferrin-bound design D formulation has significantly lower IC90 values over AMB-D for clinical isolates tested ( Figure 13A). This small feasibility study results (n = 1) indicated that transferrin can also potentially be used as targeting ligand, particularly for targeting CNS, where transferrin receptors are overexpressed during inflammation or tumor growth [39]. Similar results were observed with a dual drug loading formulation, with AMB and curcumin ( Figure 13B).…”
Section: In Vitro Efficacy Of Amb-ionp Fungal Clinical Isolates Of Casupporting
confidence: 71%
“…Tf conjugated liposomes was proposed as strategy to improve the uptake of drug in brain. Paclitaxel was delivered to mice bearing C6 glioma tumors in the brain using Tf-PEG liposomes [159]. The uptake of Tf-PEG liposomes in the brain was supported by non invasive near infrared fluorescence (NIRF) imaging.…”
Section: Transferrinmentioning
confidence: 99%
“…Transferrin was non-covalently conjugated to biotin on the distal end of the PEG spacers of the biotinylated SUVs using the procedure established in our laboratory [159]. Briefly, streptavidin was dissolved in PBS to prepare a 2 nM solution.…”
Section: Preparation Of Paclitaxel-loaded Transferrin Conjugated Targmentioning
confidence: 99%